2009
DOI: 10.1007/s12193-009-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Affect recognition for interactive companions: challenges and design in real world scenarios

Abstract: Affect sensitivity is an important requirement for artificial companions to be capable of engaging in social interaction with human users. This paper provides a general overview of some of the issues arising from the design of an affect recognition framework for artificial companions. Limitations and challenges are discussed with respect to other capabilities of companions and a real world scenario where an iCat robot plays chess with children is presented. In this scenario, affective states that a robot compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Most current social robots play the role of a companion, often in a long-term, one-on-one relationship with the user-e.g., the systems described by Breazeal [5], Castellano et al [6], and Dautenhahn [7]. In this context, the primary goal of the robot is to build a relationship with the user through social interaction: the robot is primarily an interactive partner, and any task-based behaviour is secondary to this overall goal.…”
Section: Related Workmentioning
confidence: 99%
“…Most current social robots play the role of a companion, often in a long-term, one-on-one relationship with the user-e.g., the systems described by Breazeal [5], Castellano et al [6], and Dautenhahn [7]. In this context, the primary goal of the robot is to build a relationship with the user through social interaction: the robot is primarily an interactive partner, and any task-based behaviour is secondary to this overall goal.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the work of other groups, which focused on recognition of social signals in similar interactions as in JAMES, is better comparable to our work: Scheutz et al [3] presented a framework for a robot that recognizes and generates affective behavior and evaluated parts of it on a mobile robot receptionist and waiter. Castellano et al [4] described a system to recognize affective states and attentiveness. They found that sensing the intention and affective state of the human participants is crucial for HRI.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…An overview of proposed techniques can be found in [53]. Only recently, a handful of researchers have also focused on recognizing a person's state or emotions via human body language [54][55][56][57][58][59][60][61][62][63][64]. For this discussion, we utilize the following definition of body language: the expression of emotions through human static body poses and/or body dynamics [56].…”
Section: Human Body Pose Classification Techniquesmentioning
confidence: 99%